Penerapan Senam Nifas Pada Pasien Post Sectio Caesarea Dalam Menurunkan Nyeri Pasca Persalinan - Erna Kasim; Andi Tenriola Fitri; Fitriani Fitriani (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2023)
Puerperal health services for mothers begin to be provided to competent health workers within 24 hours after giving birth. Puerperal gymnastics movement exercise is a movement that can be carried out for 24 hours after delivery through activities that the mother's condition has balanced after delivery. As for intending to establish and increase the circulation of the puerperium in the mother, it also helps the goodness of the uterine muscles after delivery. The design uses a descriptive model of the case study approach. This study used two postpartum cesarean respondents who experienced postpartum pain to perform puerperal gymnastics to reduce postpartum pain. The intervention's results on several respondents, namely puerperal gymnastics, said there was a significant change or decrease in the level of pain where the level of severe pain became the absence of pain. Mild pain (4-6) decreased to absence from severe pain (7-10), no longer presence of pain that the client's face already looks relaxed, and he does not grimace anymore. It can be concluded that there is a decrease in the pain intensity scale from mild to no more pain after being given puerperal gymnastics interventions. One of the discomforts that often arises in pregnancy is back pain. Back pain is a disorder that pregnant women widely experience throughout the pregnancy until the post-Christmas period. It should be important to encourage postpartum mothers to do puerperal gymnastics in reducing postpartum pain sectio caesarea